ANALYSIS OF E-COMMERCE ACTIVITIES THROUGH THE PROVISION OF REMOTE BANKING SERVICES - Yusufkhujaev Fazliddin Mansur ugli (American Journals, 2025)
In the context of the global digital economy, the rapid growth of e-commerce is creating demand for new formats and instruments in the financial services market. From this perspective, remote banking services (internet banking, mobile banking, electronic payment systems, and digital wallets) have emerged as an integral part of e-commerce activity. These services facilitate the exchange of goods and services in a digital environment, ensure quick settlements and payments, and help reduce transaction costs in the economy.
Keywords: Digital economy; E-commerce; Remote banking services; Information technologies; Mobile banking; Online payments; FinTech integration; Cybersecurity; Data protection; Financial inclusion; Digital infrastructure; API integration; Digital wallets; Fraud monitoring; Cu stomer experience.